2020
DOI: 10.3390/ijms21155244
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, Curcumin and Piperine Alter Human Glyoxalase 1 in MCF-7 Breast Cancer Cells

Abstract: Breast cancer is the leading cause of cancer mortality in women worldwide. Conventional cancer treatment is costly and results in many side effects. Dietary bioactive compounds may be a potential source for breast cancer prevention and treatment. In this scenario, the aim of this study was to investigate the effects of the bioactive compounds resveratrol, curcumin and piperine (R-C-P) on MCF-7 breast cancer cells and to associate them to Glyoxalase 1 (GLO1) activity. The findings indicate that R-C-P exhibits c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 62 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…A-1, A-3, and RES were primarily examined for cytotoxicity effects on these TNBC cell lines. Although other studies showed that a high concentration of RES was required to inhibit 50% of cell proliferation in breast cancer cells (MCF-7 cells IC 50 : 131 µM after 24 h treatment and IC 50 : 83.9 µM after 48 h treatment; MDA-MB-231 IC 50 : 144 µM after 24 h treatment by performing MTT assay) [47,48], we observed that low concentrations of RES and RES analogs (A-1 and A-3) were needed to kill 50% of MDA-MB-231 and MDA-MB-436 cells by using continually monitored Realtime Glo assays (Promega, Madison, WI, USA). The results indicated that A-1 had the highest cytotoxicity effect in all treatment time points, with an IC 50 of about 2 µM for both cell lines, and the low concentrations of A-1 had no significant cytotoxicity effects on the normal human breast epithelial cell line MCF-10A.…”
Section: Discussionmentioning
confidence: 95%
“…A-1, A-3, and RES were primarily examined for cytotoxicity effects on these TNBC cell lines. Although other studies showed that a high concentration of RES was required to inhibit 50% of cell proliferation in breast cancer cells (MCF-7 cells IC 50 : 131 µM after 24 h treatment and IC 50 : 83.9 µM after 48 h treatment; MDA-MB-231 IC 50 : 144 µM after 24 h treatment by performing MTT assay) [47,48], we observed that low concentrations of RES and RES analogs (A-1 and A-3) were needed to kill 50% of MDA-MB-231 and MDA-MB-436 cells by using continually monitored Realtime Glo assays (Promega, Madison, WI, USA). The results indicated that A-1 had the highest cytotoxicity effect in all treatment time points, with an IC 50 of about 2 µM for both cell lines, and the low concentrations of A-1 had no significant cytotoxicity effects on the normal human breast epithelial cell line MCF-10A.…”
Section: Discussionmentioning
confidence: 95%
“…101 Curcumin has shown anticancer mechanisms linked to lactate production, including a decline in PKM2 caused by its suppressive activity on the Warburg effect in H157 and H413 head and neck cancer (HNC) cells. Curcumin consumption also diminished the transcription of PKM1 in Cal27 human tongue squamous carcinoma cells, [102][103][104] glyoxalase I (GLO) inhibition in the presence of antimycin A in MCF-7 breast cancer cells, 105 and inhibition of Akt/mTOR signaling pathway as upstream signaling event of lactate. 106 As mentioned above, curcumin possesses inhibitory effects on glucose uptake and lactate production by downregulation of PKM2, via the inhibition of mTOR/HIF1α signaling in various cancer cell lines, for instance, lung (H1299), breast (MCF-7), cervical (HeLa), prostate (PC3), and human embryonic kidney (HEK) cells.…”
Section: Curcuminmentioning
confidence: 99%
“…Recently, it was found that the combination of resveratrol with the polyphenolic compounds such as piperine and curcumin has a signicant activity against estrogen receptor-positive MCF-7 breast cancer cells however, the authors proposed the action was accomplished through reducing glyoxalase-1 (GLO1) activity. 32,33 Considering the aforementioned ndings, a new hybrid scaffold has been designed bearing the resveratrol pharmacophoric features bound to the piperine backbone using a fragment-based drug design approach in order to target the sirtuins proteins, in particular Sirt-2, as molecular mechanism for the anticancer action of newly synthesized series, Fig. 3.…”
Section: Introductionmentioning
confidence: 99%